EUSTAR: EUROPEAN SOCIETY OF HYPERTENSION TELEMEDICINE IN ARTERIAL HYPERTENSION REGISTER 2018. (June 2018) - Schulz, E.G.; Neumann, C.L.; Middeke, M.
Abstract : Objective: Failing to reach blood pressure (BP) goals is a major problem in treatment of hypertension, causing a high socioeconomic burden, sequel morbidities and strongly increased mortality. Recent studies demonstrated that interventional decentralized telemonitoring (idTM®) can strongly improve BP management in hypertension including high risk patients. In the EDiMed-Project (efficiency analysis of services in telemedicine) - supported by German Ministry for education and research - the cost-benefit ratio was analyzed and a positive socioeconomic impact was found. Design and method: This project aims at establishing a telemonitoring system that allows to extend this service to all European Excellence centers for hypertension treatment and ultimately to all physicians treating hypertensive patients in Europe. For this effort, the unique software SciTIM® providing highest standard of data security was developed for the register to allow: Making idTM® available to physicians and patients across Europe Establishing telemedical standards for selected hypertensive indications Establishing a system for collections of high quality epidemiologic data from daily medical practice Establishing a digital interface for direct interaction between specialists and general practitioners Figure. No caption available. Results: Register nucleus started with 6 ESH-centers in 2018. The corresponding SciTIM software have been tested since May 2017 at the Nephrological Center Göttingen GbR. After completion of the test phase the EUSTAR register will be extended to other centers. To integrate data directly from the data management systems the project will generate interfaces to the most commonly used medical data management systems. In addition, system will provide a user interface to physicians, enabling to monitor their patient's telemonitoring progress at first time directly in their electronic health records and specific rules to pro-actively alert staff members via daily reports. Conclusions: The EUSTAR consortium will establish a register based on needs of medical specialists under the aegis of the ESH. A database will be created that allows safe and standardized exchange of data. The System will include interfaces for data collection from medical measurement devices and be open for all possible providers and also for other data than the first two parameters blood pressure and body weight.